Kesalahan Morfologi dalam Teks Deskripsi Karangan Peserta Didik MTsN 1 Kota Gorontalo - Rahman, Fitriyani; Malabar, Sayama; Djou, Dakia N. (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Morphology has a very important role in expressing ideas in the form of essays. However, there are many students' essays that do not pay attention to morphological aspects. The research method is descriptive qualitative. The results showed that there were (1) 10 types of morphological errors with total of 92 sentence excerpts, (2) factors causing errors, namely students' lack understanding of the rules morphological level, lack of variety in language teaching, and lack of interest in literacy. (3) solutions in minimizing errors include a direct approach, correction of classmates, habituation of morning literacy, and the use of correct Indonesian.